Lived experiences of end‐of‐life communication among nursing home staff: An interpretive phenomenological study. (29th November 2022) - Gonella, Silvia; Conti, Alessio; Albanesi, Beatrice; Antal, Alexandra; Dimonte, Valerio; Di Giulio, Paola
Abstract: Aims: To explore and understand lived experiences of end‐of‐life communication among nursing home staff. Design: Interpretive phenomenological study. Methods: In‐person, semi‐structured, in‐depth interviews were conducted from May to August 2021 with 21 nursing home staff members involved in end‐of‐life communication (four managers, four chief nurses, three chief medical officers, three nurses, three psychologists, two occupational therapists, one chief nurse aide and one nurse aide). Data were analysed by van Manen's hermeneutic approach, which uses the lifeworld existentials of spatiality, corporeality, temporality and relationality to guide reflection on the human experience. Data were reported according to the Consolidated Criteria for Reporting Qualitative Research. Results: Thirteen categories were identified and framed within the four existentials. Regarding spatiality, end‐of‐life communication took place in a physical, mental, socio‐cultural and professional competence space. With regard to corporeality, interviewees reported difficulties in managing their own feelings and those of family caregivers. For temporality, interviewees reported delays in end‐of‐life communication due to staffing issues and an increase in urgent and temporary relief admissions to nursing homes. To compensate, they tried to assure that all interactions that did take place were of high quality. Finally, with regard to relationality, interviewees lived end‐of‐life communication through their relationships with family caregivers and colleagues. The supportive role of colleagues was expressed as teamwork, which helped promote reflexivity about how to tailor communication, manage challenging emotions and situations, set aside time for communication, and prepare family caregivers for death. Conclusion: End‐of‐life communication was an all‐encompassing experience for nursing home staff. The supportive role of colleagues was stressed across all existentials, suggesting that teamwork is essential in delivering effective communication at the end‐of‐life. Patient or Public Contribution: There was no patient or public contribution to this study, which addresses the experiences of nursing home staff only.